Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

x – y = 2 2x = 3y in elimination method

Sagot :

lbva7

Answer:

x=6, y=4

Step-by-step explanation:

x - y = 2

2x = 3y => 2x - 3y = 0

x - y = 2 | ×(-2) => -2x + 2y = -4

2x - 3y = 0

-2x + 2y = -4

2x - 3y = 0

___________

0 - y = - 4 | ×(-1)

y = 4

Substitution in x - y = 2:

x - 4 = 2 | +4

x = 2+4 = 6